Adaptive spatial mode of space-time and spacefrequency OFDM system over fading channels - Noordin, Nor K.; M. Ali, Borhanuddin; Jamuar, S. S.; A. Rahman, Tharek; Ismail, Mahamod (Penerbit UTM Press, 2006)
In this paper we present a 2 transmit 1 receive (1 Tx : 1 Rx) adaptive spatial mode (ASM) of space-time (ST) and space-frequency (SF) orthogonal frequency division multiplexing (OFDM). At low signal to noise ratio (SNR) we employ ST-OFDM and switch to SF-OFDM at a certain SNR threshold. We determine this threshold from the intersection of individual performance curves. Results show a gain of 9 dB (at a bit error rate of 10-3) is achieved by employing adaptive spatial mode compared to a fixed ST-OFDM, almost 6 dB to fixed SF-OFDM, 4 dB to Coded ST-OFDM and 2 dB to a fixed coded SF-OFDM, at a delay spread of 700 ns.